The Effect of Team Games Tournament in Biology for Students in Second Semester Grade XI of SMAN 15 Medan Academic Year 2014/ 2015 on Their Learning Outcome, Motivation, and Retention - Ratih Oktaviani Ginting; Syarifuddin Syarifuddin (Universitas Negeri Medan, 2015)
The aims of this research were investigated the effect of Team Games Tournament on students’(1) Motivation, (2) Learning Outcome, (3) Memory Retention. Two classes of students from oneschool in Medan as control (conventional learning) and experimental class (TGT). Students’leaning outcome were measured with multiple choice and essay test (pretest and post- test).Data of students’ motivation were derived from questionnaire filled by students, and studentsmemory retention were measured by retention test after 21 days. The data were analyzed withANCOVA by using SPSS v.19 software package for Windows, AnatesV4- New software, andSYSTAT. Results showed that Team Games Tournament did not have significantly affectedstudents’ model (F= 0.771; P= 0.383), corrected model (F=1.532; P= 0.214 ), sex (F= 0.930; P=0.338) and the interaction between model and sex (F= 1.612 ; P= 0.208) but, it was significantin the students intercept (F=3523.514 , P= 0.000) for the motivation of students in pretest. Thecorrected model (F= 11.774; P= 0.000), intercept (F= 4923.363; P= 0.000), and model (F=30.042; P= 0.000) were very significant, but sex (F= 0.489; P= 0.486) and the interactionbetween model and sex (F= 0.25; P= 0.874) were not significant for motivation of students inpost- test. The corrected model (F= 1.667; P= 0.182), model (F= 0.277; P= 0.601), sex (F=3.488; P= 0.66), and interaction between model and sex (F= 0.216; P= 0.274) were notsignificant, but it was significant in students intercept (F= 4505.125; P= 0.000) for learningoutcome in pretest. The corrected model (F= 14.067; P= 0.000), intercept (F= 11908.631; P=0.000), model (F= 14.433; P= 0.000), sex (F= 4.979; P= 0.000), and interaction between modeland sex (F= 4.979; P= 0.29) were very significantly for learning outcome of students in posttest,and the corrected model (P= 90.968; F= 0.000), intercept (P= 53702.422; F= 0.000), model(P= 196.175, F= 0.000), and intercation between model and sex (P= 10.414; F= 0.002) weresignificant, but it was not significant for sex (F= 0.216, P= 0.643) to students’ memory retentionKeyword : Motivation. Learning Outcome, Retention, Team Games Tournament